First study of extended half-life rFVIIIFc in previously untreated patients with hemophilia A: PUPs A-LONG final results - Königs, Christoph; Ozelo, Margareth C.; Dunn, Amy; Kulkarni, Roshni; Nolan, Beatrice; Brown, Simon A.; Schiavulli, Michele; Gunawardena, Sriya; Mukhopadhyay, Sutirtha; Jayawardene, Deepthi; Winding, Bent; Carcao, Manuel (Blood, 2022)
PUPs A-LONG evaluated safety and efficacy of recombinant factor VIII Fc fusion protein (rFVIIIFc) in previously untreated patients (PUPs) with hemophilia A. This open-label, Phase 3 study enrolled male PUPs (<6 years) with severe hemophilia A to receive rFVIIIFc. The primary endpoint was occurrence of inhibitor development. Secondary endpoints included annualized bleed rate (ABR). Of 103 subjects receiving ≥1 dose of rFVIIIFc, 80 (78%) were aged <1 year at study start, 20 (19%) had family history of inhibitors, and 82 (80%) had high-risk F8 mutations. Twenty subjects began on prophylaxis, while 81 began an on-demand regimen (69 later switched to prophylaxis). Eighty-seven (81%) subjects completed the study. Inhibitor incidence was 31.1% (95% confidence interval [CI]: 21.8%–41.7%) in subjects with ≥10 exposure days (or inhibitor); high-titer inhibitor incidence was 15.6% (95% CI: 8.8%–24.7%). The median (range) time to high-titer inhibitor development was 9 (4–14) exposure days. Twenty-eight (27%) subjects experienced 32 rFVIIIFc treatment-related adverse events; most were inhibitor development. There was 1 non–treatment-related death due to intracranial hemorrhage (onset prior to first rFVIIIFc dose). The overall median (interquartile range) ABR was 1.49 (0.00–4.40) for subjects on variable prophylaxis dosing regimens. In this study of rFVIIIFc in pediatric PUPs with severe hemophilia A, overall inhibitor development was within expected range, although high-titer inhibitor development was on the low end of the range reported in literature. rFVIIIFc was well-tolerated and effective as prophylaxis and for treatment of bleeds. This trial is registered at www.clinicaltrials.gov (NCT02234323).